2005
DOI: 10.1002/ajmg.a.30599
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fibroblast growth factor‐23 in hypophosphatemic linear nevus sebaceous syndrome

Abstract: We report on an adolescent who experienced the onset of linear nevus sebaceous syndrome (LNSS) prior to 1 year of age. At 7 years of age he was diagnosed to have hypophosphatemic rickets. He was suboptimally controlled with phosphate and calcitriol treatment and sustained numerous insufficiency fractures ipsilateral to the linear sebaceous nevus. Fibroblast growth factor-23 (FGF-23), the phosphaturic peptide, was elevated in the plasma. Treamtent with the somatostatin agonist, octreotide, and excision of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 42 publications
3
55
2
Order By: Relevance
“…A subset of these patients have ipsilateral focal bone disease associated with hypophosphatemic rickets, elevated circulating FGF23 levels, and aberrant 1,25(OH) 2 D levels, similar to other syndromes that are caused by elevated FGF23. Treatment with the somatostatin agonist octreotide and excision of the nevus have been reported to normalize FGF23 (63)(64)(65).…”
Section: Sporadic/acquired Disordersmentioning
confidence: 99%
“…A subset of these patients have ipsilateral focal bone disease associated with hypophosphatemic rickets, elevated circulating FGF23 levels, and aberrant 1,25(OH) 2 D levels, similar to other syndromes that are caused by elevated FGF23. Treatment with the somatostatin agonist octreotide and excision of the nevus have been reported to normalize FGF23 (63)(64)(65).…”
Section: Sporadic/acquired Disordersmentioning
confidence: 99%
“…Its physiological importance is exemplified by numerous activating and inactivating mutations in the human FGF23 gene, causing two clinical disorders of disturbed Pi homeostasis: autosomal dominant hypophosphatemic rickets (ADHR, OMIM#193100; ADHR-Consortium 2000) and hyperphosphatemic familial tumoral calcinosis (HFTC, OMIM#211900; Benet-Pages et al 2005, Larsson et al 2005. Elevated FGF23 levels are also associated with several other disorders of hypophosphatemia or dysfunctional regulation of vitamin D, such as autosomal recessive hypophosphatemic rickets (ARHR; Feng et al 2006, Lorenz-Depiereux et al 2006, X-linked hypophosphatemic rickets (XLH; Liu et al 2003, Riminucci et al 2003, tumor-induced osteomalacia (TIO; Shimada et al 2001, White et al 2001b, fibrous dysplasia (FD; Riminucci et al 2003), and linear nevus sebaceous syndrome (LNSS; Hoffman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic mechanism involved in the onset of hypophosphataemic rickets in ENS is not fully clarified. It has been proposed that FGF23 is the putative phosphatonin, based on demonstration of its elevated blood levels in a patient with LNSS (56). Subsequent studies also found the same result (119)(120).…”
Section: Linear Nevus Sebaceous Syndrome (Lnss)mentioning
confidence: 85%
“…Genetic disorders include Xlinked dominant hypophosphatemic rickets, autosomal recessive hypophosphatemic rickets (35, 50-51), autosomal dominant hypophosphatemic rickets (1), hypophosphatemic rickets associated with McCune-Albright syndrome (52-54) and Linear sebaceous nevus syndrome (55)(56)(57). Acquired disorders include tumor induced osteomalacia.…”
Section: High Fgf23 and Disorders With Abnormal Phosphate Metabolismmentioning
confidence: 99%